Pulmonary Artery Intimal Sarcoma Diagnosed Preoperatively by Endovascular Biopsy and Treated via Right Pneumonectomy and Pulmonary Arterioplasty - Daiki Kato; Shohei Mori; Eriko Harada; Rintaro Shigemori; Takamasa Shibazaki; Hideki Matsudaira; Jun Hirano; Hirokazu Ashida; Hiroko Kimura; Michio Yoshitake; Takashi Kunihara; Takashi Ohtsuka (Case Reports in Pulmonology)
Introduction. Intimal sarcoma is a very rare tumor arising within the intima of the pulmonary artery. Preoperative diagnosis of pulmonary artery sarcoma is difficult, and the tumor is sometimes misdiagnosed as pulmonary thromboembolism. We report a case of pulmonary artery intimal sarcoma successfully diagnosed by preoperative endovascular biopsy and treated via right pneumonectomy and pulmonary arterioplasty. Presentation of a Case. A 72-year-old woman was referred to our hospital with a low-attenuation defect in the lumen of the right main pulmonary artery by computed tomography. Pulmonary artery thromboembolism was suspected, and anticoagulation therapy was administered. However, the defect in the pulmonary artery did not improve. Endovascular catheter aspiration biopsy was performed. Histological examination revealed pulmonary artery sarcoma. The patient was treated with right pneumonectomy and arterioplasty with the use of cardiopulmonary bypass. Discussion. Preoperative biopsy by endovascular catheter is worth considering for a patient with a tumor in the pulmonary artery and can help in planning treatment strategies.